Increasing the Customer Retention Rate with Digital Banking Performance Optimization during the Covid-19 Pandemic (Study at BMT Amanah Ummah in Kartasura, Sukoharjo) - Istiatin Istiatin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Customer retention is the maintenance of sustainable business relationships with customers over the long term. A high customer retention rate is inversely proportional to customers leaving the company (defection). Entering the industrial era 4.0, where all economic activities began to shift to all digital, financial institutions were required to adapt, including Baitul Maal wat Tamwil (BMT). As a financial institution that has played an important role in the development of the Islamic economy, it has become a necessity for BMT to adapt to this change. The economic slowdown due to Covid-19 has reduced payment activity, but has accelerated the adoption of digital financial technology. The purpose of this study is to provide an overview of the implementation of digital banking by BMT Amanah Ummah as one of the steps in retaining its customers during this covid-19 pandemic. The method used in this study was a qualitative descriptive analysis technique, which seeks to describe the condition of digital banking at BMT during the COVID-19 pandemic where all data generated and presented are in the form of descriptions. The results of this study, BMT seeks to retain customers by optimizing the application of digital banking with BMT Mobile in its operations during this covid-19 pandemic. In line with the widespread use of digital instruments during the pandemic, digital economic and financial transactions continue to grow. In its application there are already various digitization used by BMT. With mobile BMT, BMT members can access data and transaction needs, ranging from checking balances, savings, principal savings, mandatory savings, voluntary savings, checking transaction history, and checking accounts Keywords: Customer retention, Digital banking, Covid 19, BMT Amanah Ummah